Macromol. Rapid Commun. 9/2016. Issue 9 (May 2016) - Nguyen, Diep; Adnan, Nik Nik M.; Oliver, Susan; Boyer, Cyrille
Abstract : Front Cover: Carbon monoxide has recently been discovered as an endogenous signalling molecule, which is naturally produced by the action of heme oxygenase 1 and 2 on the heme from hemoglobin breakdown. Following the first report that carbon monoxide is a normal neurotransmitter, numerous reports have demonstrated its important actions in biological systems to prevent diseases. Here, the specific delivery of carbon monoxide using polymeric nanoparticles is demonstrated. Further details can be found in the article by D. Nguyen, N. N. M. Adnan, S. Oliver, and C. Boyer* on page 739.